The Postdoctoral Plan for the Education and Training of Counsellors - Mahrer, Alvin R.; Boulet, Donald B. (Canadian Journal of Counselling and Psychotherapy, 2011)
The purpose of this paper is to propose a postdoctoral plan for the education and training of counsellors who seek advanced knowledge and competence in psychotherapy. In support of this plan, seven propositions are submitted on the current status of pregraduate and postgraduate education and training of psychotherapists. Based upon a study of the programs of approximately 100 postgraduate training centres, a set of minimal standards is proposed for the postdoctoral training of psychotherapists. Implications are drawn for the field of counsellor education and training.